2003
DOI: 10.1046/j.1365-2249.2003.02062.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infection suppresses IFN-γproduction ofγδT cells

Abstract: SUMMARYThe immunological mechanisms by which respiratory syncytial virus (RSV) contributes to the development of asthma are poorly understood. gd T cells are important in mucosal defence, and may contribute to the establishment of primary immune responses by producing cytokines early during respiratory infections. Thus, we used flow cytometry and intracellular cytokine staining to investigate the expression of interferon (IFN)-g and interleukin (IL)-4 by mitogen-stimulated gd T cells from the peripheral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…However, our data further showed that abundant IFN-␥ was released by H5N1-infected mast cells in vitro. It has been well documented that influenza virus induces high levels of IFN-␥ in the lungs of infected animals, which is believed to be produced mainly by T and NK cells (1,42). In the present study, we demonstrated that mast cells released a high level of IFN-␥ after H5N1 virus infection in vitro, and this is believed to be the first report that IFN-␥ can be produced by activated mast cells, in addition to T and NK cells, in H5N1 virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, our data further showed that abundant IFN-␥ was released by H5N1-infected mast cells in vitro. It has been well documented that influenza virus induces high levels of IFN-␥ in the lungs of infected animals, which is believed to be produced mainly by T and NK cells (1,42). In the present study, we demonstrated that mast cells released a high level of IFN-␥ after H5N1 virus infection in vitro, and this is believed to be the first report that IFN-␥ can be produced by activated mast cells, in addition to T and NK cells, in H5N1 virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…In response to various bacterial and viral infections, ␥␦ T cells can rapidly produce cytokines, such as IFN-␥, TNF-␣, and IL-17 (82,(102)(103)(104)(105). However, mechanisms by which these pathogens elicit cytokine responses in ␥␦ T cells are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Teng, Whitehead, and colleagues (346,378) have demonstrated the attenuation of hRSV NS-1 and M2-2 or NS-1 and SII deletion mutants in the chimpanzee model of infection, although without specific reference to interferonrelated phenomena. Interestingly, hRSV is sensitive to inhibition by gamma interferon (11,20,39,99,276,365), and potential hRSV-mediated modulation pathways have been identified (6,17).…”
Section: Virus Evasion Of Innate Immunitymentioning
confidence: 99%